Arthroscopic Treatment of Discoid Lateral Meniscus Tears in Children With Achondroplasia. Issue 5 (July 2016) - Atanda, Alfred; Wallace, Maegen; Bober, Michael B.; Mackenzie, William
Abstract : Background: Achondroplasia is the most common form of skeletal dysplasia that presents to the pediatric orthopaedist. More than half of achondroplasia patients are affected with knee pain. It is thought that the majority of this pain may be due to spinal stenosis, hip pathology, or knee malalignment. Discoid menisci can be a source of lateral knee joint pain in skeletally immature patients in general. We present the first case series of patients with achondroplasia who had symptomatic discoid lateral menisci treated with arthroscopic knee surgery. Methods: The charts of 6 patients (8 knees) with achondroplasia who underwent arthroscopic knee surgery for symptomatic discoid lateral menisci were collected. History and physical examination data, magnetic resonance imaging findings, and operative reports were reviewed. Meniscal tear configuration and treatment type (meniscectomy vs. repair) were noted. Results: Each patient was found to have a tear of the discoid meniscus. All menisci were treated with saucerization. In addition, meniscal repair was performed in 2 cases, partial meniscectomy in 3 cases, and subtotal meniscectomy in 3 cases. Two patients had bilateral discoid meniscal tears which were treated. Average follow-up was 2.4 years (range, 1 to 4.5 y) and the average pediatric International Knee Documentation Committee (pedi-IKDC) score was 85.3% (range, 75% to 95.4%). At final follow-up, all patients were pain free and able to return to full activities. Conclusions: Discoid meniscus tears may be a source of lateral joint line pain in patients with achondroplasia. These injuries can be successfully treated with arthroscopic surgery in this patient population. Future studies need to be done to determine the exact incidence of discoid menisci in achondroplasia patients and also to determine whether there is a genetic relationship between the 2 conditions. Level of Evidence: Level IV—case series.